Kako razvijati družinsko pismenost v predšolskem obdobju - Licardo, Marta; Haramija, Dragica (2017)
How to develop family literacy in preschool period. Booklet of good practices with the title »How to develop family literacy in preschool period« is a result of the project »Hugged by Words, program for promoting family literacy«, which was implemented by the Faculty of Education and Faculty of Arts University of Maribor, during the years 2016 and 2017. The booklet includes good practices which were implemented in kindergartens included in the project and also some practices from other kindergartens. Presented good practices include guided activities for children (from one to three and four to six years old) and their parents. Most cases include integration of various curricular fields. Emphasis is on practices that have increased interest in the use of picture books in children and parents, to encourage reading, listening and storytelling and include various adaptations and dramatizations. Workshops for parents and children are presented, as well as individual games that parents can use to promote family literacy. From examples of good practices, it is possible to understand how to promote family literacy and how to implement activities that contribute to learning about new concepts, language development, pre-writing skills and reading literacy in pre-school and early school period. The collection is intended for all professionals in kindergartens and in the first three years of elementary school and parents who have children in this developmental period, as it combines examples of good practices that can be implemented with children in kindergarten/school and in home environment.
Keywords: family literacy; early literacy; reading literacy; good practices; preschool education